Edukasi Pendekatan Sosial Berbasis Ekologis dan Ekonomi Pada Pelestarian Lamun di Kawasan Taman Wisata Perairan Bintan Kecamatan Gunung Kijang - Hasan, Elsa Nursyifa; Hardianti, Heni; Bachtiar, Aidin Fitrah (Jurnal Empirika, 2025)
This article discusses the importance of educating ecologically and economically based social approaches in seagrass conservation in Taman Wisata Perairan Bintan, Kecamatan Gunung Kijang. The problems raised are the low awareness of the community on the importance of seagrass ecosystems and the effectiveness of the approaches used in conservation. This study aims to analyze and compare the effectiveness of ecological and economic approaches in involving coastal communities in seagrass conservation. The method was descriptive with a qualitative approach, including in-depth interviews to understand the community's views. The results show that the economic approach is more effective in encouraging community participation, with financial incentives increasing their awareness and involvement. In contrast, the ecological approach still faces challenges due to the community's low understanding of the long-term benefits of seagrass conservation. Combining these two approaches is proposed to achieve more optimal results in marine ecosystem conservation.